Hand Sludging: A Report from North West Bengal. - Ball, Peter D.; Danert, Kerstin (Cranfield University, 1999)
The Low Cost Drilling Project (Cranfield University/DFID/Government of Uganda) is developing a modification of the traditional Asian sludging technology for use in Africa. As part of the technology research a visit was made to north India to observe and measure various characteristics of this well drilling technique. The report describes these observations and draws conclusions for the Low Cost Well Drilling Project.